Load optimization on the performance of combined cycle power plant Block 4 PT Indonesia Power Priok POMU - Louise Indah Utami; Ika Yuliyani; Yanti Suprianti; Purwinda Iriani (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2022)
Combined cycle power plant (CCPP) is a closed-cycle power plant, where the heat from the gas turbine’s (GT) exhaust gas will be streamed to the heat recovery steam generator (HRSG) to be utilized by steam turbine (ST). CCPP Block 4 (Jawa-2) PT Indonesia Power Priok POMU has an installed capacity of 880 MW, consists of 2 GT units (301.5 MW each) and 1 ST unit (307.5 MW). The performance of a power plant depends on its load, as the efficiency of the turbine generator is low when operated at low loads. The data as of July 2019 showed that 2.2.1 (2 GT, 2 HRSG, 1 ST) configuration has been used in three conditions where the CC net load was around 30 - 45 %, which in fact could be compensated by the 1.1.1 (1 GT, 1 HRSG, 1 ST) configuration. This resulted in a decrease of the CC net efficiency up to 21.34 %. The optimization that can be done is to change the load configuration from 2.2.1 to 1.1.1 at 0 - 50 % of CC net load through simulations, by including the influence of the GT and HRSG start-up processes. The result of this optimization is that the CCPP performance increases due to higher performance of each turbine generator. Thus, the optimization results during July 2019 provided energy saving of 1,146.09 MMBTU or equivalent to cost saving of IDR 152,249,551.76.